2022
DOI: 10.1055/s-0042-1751354
|View full text |Cite
|
Sign up to set email alerts
|

The Awakening of a Sleeping Beauty: The ortho Photocycloaddition in the Total Synthesis of Protoilludane- and Prezizaene-Type ­Sesquiterpenes

Abstract: Photochemical cascade (domino) reactions provide a unique opportunity for the construction of complex molecular architectures. Specifically, an intramolecular ortho photocycloaddition of 7-(alkenyloxy)-indanones triggers a sequence of consecutive reactions that can lead in a single operation to the complete skeleton of two important classes of sesquiterpenes: protoilludanes and prezizaenes. In the former case, two transformations follow the initial photocycloaddition, while in the latter case, there are three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Although this product diversity can serve as an ideal platform to explore the 3D chemical space, controlling the selectivity remains a fundamental challenge. While direct irradiation of benzenoids with usually harsh UV light populates their excited singlet state (S 1 ), which predominantly reacts with ground-state (S 0 ) alkenes in a concerted pathway to the meta -product, unlocking the diradical character of the triplet excited state (T 1 ) allows for a stepwise radical mechanism to the ortho - or para -product. , However, accessing the T 1 state from the S 1 state is plagued with competing side reactions before the intersystem crossing (ISC) event. In this vein, visible light-mediated triplet–triplet energy transfer (EnT) catalysis proved to be a powerful and especially mild tool to reach the substrate’s T 1 state directly from its S 0 state using a suitable photosensitizer. Recently, our group became interested in the development of photocycloadditions of bicyclic aza-arenes including quinolines, quinazolines, and quinoxalinescore motifs in a broad spectrum of natural products, pharmaceuticals, and materials science (Scheme A) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this product diversity can serve as an ideal platform to explore the 3D chemical space, controlling the selectivity remains a fundamental challenge. While direct irradiation of benzenoids with usually harsh UV light populates their excited singlet state (S 1 ), which predominantly reacts with ground-state (S 0 ) alkenes in a concerted pathway to the meta -product, unlocking the diradical character of the triplet excited state (T 1 ) allows for a stepwise radical mechanism to the ortho - or para -product. , However, accessing the T 1 state from the S 1 state is plagued with competing side reactions before the intersystem crossing (ISC) event. In this vein, visible light-mediated triplet–triplet energy transfer (EnT) catalysis proved to be a powerful and especially mild tool to reach the substrate’s T 1 state directly from its S 0 state using a suitable photosensitizer. Recently, our group became interested in the development of photocycloadditions of bicyclic aza-arenes including quinolines, quinazolines, and quinoxalinescore motifs in a broad spectrum of natural products, pharmaceuticals, and materials science (Scheme A) .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we reported that tuning the substituents enables the construction of complex pyridine-fused 2D/3D ring systems via a cascade involving an ortho -cycloaddition with a subsequent rearrangement initiated by a second EnT . Despite the synthetic appeal of such cascade reactions, the photolability of the first addition products containing strained (four-membered) rings adjacent to an excitable alkene consequently hampers their synthetic access. , Thus, it is not surprising that intermolecular ortho -photocycloadditions of benzenoids that suppress a consecutive rearrangement are still underrepresented in the literature . We questioned whether a strain-release approach could serve as a thermodynamical pitfall to conserve the original ortho -adduct by forming cycloaddition products with a reduced tendency to undergo downstream rearrangements or cycloreversion (Scheme C) .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Bach illustrates the potential of photochemical cascade (domino) reactions as a means to rapidly and reliably construct molecular architectures of utmost complexity in a single operation. 33 Similarly, Bower describes the potential of minimally activated cyclopropanes to generate active inter-…”
Section: Cluster Synlettmentioning
confidence: 99%
“…In particular, Bach illustrates the potential of photochemical cascade (domino) reactions as a means to rapidly and reliably construct molecular architectures of utmost complexity in a single operation. 33 Similarly, Bower describes the potential of minimally activated cyclopropanes to generate active intermediates by means of C–C bond cleavage as a vehicle for building up molecular complexity. 34 On the other hand, the versatility of Cp*Co(III) catalysis in a series of C–H amination events is nicely delineated by Chang, including detailed mechanistic investigations.…”
mentioning
confidence: 99%
“…We found that 7-alkenyloxy-substituted 1-indanones provide a remarkably efficient entry into the protoilludane class of natural products if irradiated at long wavelength (λ > 350 nm) . At shorter wavelength (λ = 350 nm), a third photon initiates a di-π-methane rearrangement reaction which eventually delivers a pentacyclic product. , Compound rac - 1 for example gave strained cyclopropanes rac - 2a and rac - 2b in a total yield of 62% (Scheme ). Putative intermediates of the reaction sequence en route to product rac - 2a derive from initial ortho -photocycloaddition (int 1a ), followed by a disrotatory cyclohexadiene ring opening (int 2a ).…”
mentioning
confidence: 99%